Resolution of a generic cubic

Algebra Level pending

for a generic equation ( a ( x 3 ) ) + ( b ( x 2 ) ) + ( c x ) + d = 0 (a(x^3))+(b(x^2))+(cx)+d=0 .... then ( x 3 ) ( 3 ( x 2 ) ) + 3 x 1 = 0 (x^3)-(3(x^2))+3x-1=0 has solution ....

1 -1 (sqrt(2))/2 -2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

There are 2 ways.... the first ( x + a ) 3 = x 3 + 3 x 2 a + 3 x a 2 + a 3 = 0 (x+a)^3=x^3+3x^2a+3xa^2+a^3=0 then for comparison you obtain the aswer... the second is by this metod

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...